The effect of dental bleaching on pulpal tissue response in a diabetic animal model - Cintra, Luciano Tavares Angelo [UNESP]; Ferreira, L. L. [UNESP]; Benetti, F. [UNESP]; Gastélum, A. A.; Gomes Filho, João Eduardo [UNESP]; Ervolino, Edilson [UNESP]; Briso, André Luiz Fraga [UNESP] (Wiley, 2017)
Aim: To evaluate pulpal tissue response after dental bleaching in normal and alloxan-induced diabetic rats. Methodology: Twenty-eight rats were divided into two groups of normoglycaemic and diabetic rats (n = 14). Diabetes mellitus (DM) was induced with alloxan. After DM confirmation, all rats were anaesthetized and dental bleaching was performed with 35% hydrogen peroxide (H2O2) on the right maxillary molars for 30 min. Left molars were used as controls. Bleaching resulted in four hemimaxillae groups: normoglycaemic (N), N-bleached (NBle), diabetic (D) and D-bleached (DBle). After 2 or 30 days, the animals were euthanized and the hemimaxillae were removed, processed for histopathological analysis and stained with haematoxylin–eosin (HE), Masson's trichrome (MT) and picrosirius red (PSR). Results obtained within animals (normoglycaemic or diabetic rats) were submitted to Wilcoxon or paired t-tests, and between animal (normoglycaemic and diabetic rats), to Mann–Whitney test or t-tests. Results: At 2 days, the NBle group had a mild inflammatory infiltration in the pulpal tissue, whilst the DBle had severe inflammation or necrosis (P < 0.05). At 30 days, no inflammation was present. However, a significant difference in pulp chamber area reduction by reactionary dentine deposition was found between the NBle and DBle groups (P < 0.05). At 2 days, fewer immature collagen fibres and more mature collagen fibres were noted in the NBle, D and DBle groups; this was significantly different when compared to the N group (P < 0.05). At 30 days, significantly fewer immature collagen fibres and more mature collagen fibres were noted in NBle compared with DBle group (P < 0.05). Conclusions: The inflammatory tissue response in rats’ teeth after dental bleaching was greater in diabetic rats. Additionally, the increase in reactionary dentine deposition and mature collagen fibres observed in diabetic rats needs further evaluation to confirm the present results.
Keywords: collagen; dental bleaching; inflammatory response; reactionary dentine